Paris–Rome–London. Information and Propaganda Campaign for the Polish Question prior to the Great War (1907–14) - Sikorski, Tomasz; Wątor, Adam (Acta Poloniae Historica, 2022)
The article reconstructs Polish information and propaganda campaigns in Western Europe in the run-up to the Great War. Those initiatives allowed the issues related to the Polish question, especially the persecution of Poles under the Prussian and Russian partitions, to be brought to public attention in the West. The authors trace the process of disseminating information to the intellectual communities of Paris, Rome and London based on participant accounts, reports, propaganda pamphlets, the press from the period and secondary literature. They conclude that propaganda campaigns reached a relatively narrow group of intellectuals, writers, members of the artistic community, journalists, and to a lesser extent, parliamentarians. Although the information campaign could not immediately alter the previously established stereotypes, its specific effects could be observed during the Great War and at the Paris Peace Conference.